Novel integration of carbon counter electrode based perovskite solar cell with thermoelectric generator for efficient solar energy conversion. (August 2017) - Liu, Zhiyong; Sun, Bo; Zhong, Yan; Liu, Xingyue; Han, Jinghui; Shi, Tielin; Tang, Zirong; Liao, Guanglan
Abstract: We demonstrate a novel integration of carbon counter electrodes based perovskite solar cells (PSCs) and thermoelectric generators (TEs), which exhibits excellent thermal endurance and photo-electric conversion by use of good light-harvesting capabilities over the wide sunlight spectra. The carbon counter electrode based PSC owns a good prospect in development and commercialization, whereas photo-thermal effects induced thermal degradation will be more crucial due to notable photo-thermal conversion of the carbon. The photovoltaic performance of the PSCs will decline when the temperature increases and recover when decreasing. After integration with TEs, the carbon electrodes can act as the infrared light absorption layer for the TEs, which improve the photo-thermal ability and triple the output voltage of the thermoelectric devices, substantially compensating the thermal degradation of the PSCs. Electrical measurements reveal that the integrated devices exhibit much higher and more stable energy output. When tested in ambient air, the hybrid device exhibits obvious enhancement: the overall conversion efficiency increases from 9.88% to 12.6% after integration. When the cold side of the TE part is cooled by ice bath, the hybridization obtains a maximum V OC of 1.87 V under AM 1.5 G illumination with a temperature gradient of 15 °C, boosts a more than 124% increase of the photo-electric conversion efficiency (PCE), from 9.88% (photovoltaic) to 22.2% (photovoltaic-thermoelectric), and gets a higher maximum power output of 22.2 mW cm −2 . By further optimization, larger improvements in PCE of the integration can be achieved. Our work opens up new avenues for the realization of high-performance, wide sunlight-harvesting photovoltaic-thermoelectric hybrid devices. Graphical abstract: A photovoltaic-thermoelectric integrated device composed of a perovskite solar cell and a thermoelectric generator is demonstrated for efficient solar energy conversion. Highlights: A novel integration of carbon counter electrode based perovskite solar cell and thermoelectric generator was reported. The integration broadened the use of solar spectra since the excellent light absorption property of carbon. Thermal endurance of the integrated devices was studied. The champion integrated device with efficiencies of 22.2% (in ice bath) and 12.6% (in ambient air) exhibited efficient solar energy utilization.